Natural Material Media in Early Childhood Collage Art Creativity: Study of Local Cultural Learning with a Qualitative Approach - Nur Fajrie; Ahmad Hariyadi; Heradini Faizah; David Evans; Mark Jhon Prestoza; Hendri Pratama (Journal of Innovation in Educational and Cultural Research, 2024)
Early childhood education (ECE) is a pivotal stage in human development, establishing the groundwork for lifelong learning and holistic growth. Children acquire foundational academic skills during this period while developing crucial social, emotional, and cognitive abilities. This study investigates the effectiveness of collaborative learning with parents in enhancing children's creative abilities in creating collage art using natural materials in kindergartens in Central Java. Participants included 15 kindergarten students, 10 teachers, five principals, and two parents. Data were collected through interviews, documentation, and questionnaires to capture in-depth participant experiences. The Findings indicate that using natural materials—such as leaves, seeds, and twigs—stimulates children's creativity, fine motor skills, and cognitive development. Additionally, it fosters stronger relationships among children, parents, and the school community, contributing to a holistic educational experience. This research emphasizes the significance of utilizing natural materials in early childhood collage art to foster creativity while incorporating local cultural values. The implications of this research extend to education policies, encouraging the adoption of culturally relevant teaching methods and educators seeking innovative strategies to blend creativity, sustainability, and cultural identity in early learning.